Semi-solid sodium ion hard carbon negative electrode material and preparation method thereof, and battery

By forming Na-Sn-Al-O-based compounds on the surface of the hard carbon negative electrode sheet, the problem of SEI film formation consuming a large amount of active sodium ions during the first charge and discharge of the hard carbon negative electrode material is solved, and the effect of improving the circulation performance and energy density of semi-solid sodium ion batteries is achieved.

CN119481049BActive Publication Date: 2025-04-29SHANDONG ZHAOWEN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510046859.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

In existing semi-solid sodium ion batteries, the formation of the hard carbon negative electrode material consumes a large amount of active sodium ions during the first charge and discharge process, resulting in low efficiency of the first cycle and poor energy density and cycling performance.

Method used

By forming a Na-Sn-Al-O-based compound on the surface of the hard carbon negative electrode sheet, the Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder are contacted in the first electrolyte for pre-sodiumization, forming a stable SEI protective layer, increasing the transfer rate of sodium ions and inhibiting the formation of sodium dendrites.

Benefits of technology

The circulation performance and energy density of semi-solid sodium ion batteries are significantly improved, the first cycle efficiency is improved, and the side reaction between the electrolyte and hard carbon is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481049B_ABST
    Figure CN119481049B_ABST
Patent Text Reader

Abstract

The present invention discloses a semi-solid sodium-ion hard carbon negative electrode material, a preparation method thereof, and a battery, which belong to the technical field of semi-solid sodium-ion batteries. The preparation steps are as follows: a Na-Sn metal sheet and a hard carbon negative electrode sheet containing Al2O3 powder are contacted in a first electrolyte environment for pre-sodiation to obtain a negative electrode material, and the first electrolyte contains a sodium salt and an organic solvent. By the direct contact method, a Na-Sn-Al-O structure capable of stably releasing active sodium is formed on the surface of the hard carbon negative electrode sheet. This structure has a synergistic effect and can serve as a thin and uniform SEI protective layer, improving the transmission speed of sodium ions, avoiding the continuous consumption of the electrolyte during the cycling process, making up for the loss of sodium ions during the first charge-discharge process of the layered oxide, improving the first-cycle efficiency of the battery, and at the same time separating the surface of the hard carbon from the electrolyte, effectively suppressing the continuous side reaction between the electrolyte and the hard carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semi-solid sodium ion batteries, and in particular to a semi-solid sodium ion hard carbon negative electrode material and a preparation method thereof, and a battery. Background Art

[0002] With the reduction of fossil fuels and people's concern about environmental issues, electrochemical energy storage systems have begun to be highly anticipated. Sodium resources are abundant, and sodium has similar chemical and electrochemical properties to lithium, so sodium-ion batteries have become the most ideal substitute for lithium-ion batteries. Compared with sodium-ion batteries with liquid electrolytes, semi-solid sodium-ion batteries can effectively avoid the safety issues of flammable and explosive liquid electrolytes, and prevent safety issues caused by electrolyte leakage during battery collision and puncture.

[0003] The hard carbon anode is considered to be one of the most promising anode materials for sodium-ion batteries due to its cost advantage, high sodium storage capacity and low sodium storage potential. However, the formation of the SEI film during the first charge and discharge process of the hard carbon anode consumes a large amount of active sodium ions, which reduces the first cycle coulombic efficiency of the hard carbon anode and the energy density of the sodium-ion battery. Especially in the layered oxide of the P2 phase, due to the orderly vacancies, the sodium ions released from the positive electrode in the first cycle are far from enough to inject enough sodium ions into the hard carbon side, and the first cycle coulombic efficiency (first efficiency) of the positive electrode is far less than 100%. This results in a low first efficiency of the whole battery. At the same time, when the SEI structure formed in the first cycle is uneven, it is very easy to cause the subsequent cycles to continue to consume active sodium, causing the cycle performance to continue to decay. Therefore, the pre-sodiumization of the hard carbon anode is of great significance for improving the full battery specific capacity, energy density and cycle performance of semi-solid sodium-ion batteries.

[0004] In the prior art, the electrochemical pre-sodium method is to assemble a half-cell on the surface of the negative electrode in advance for charging and discharging, thereby generating a SEI film on the surface of the negative electrode, and then disassemble the negative electrode sheet that has been electrochemically pre-sodiumized for use in a full battery. However, the operation is cumbersome and has many restrictions, so it cannot be used in industrial production.

[0005] The pre-sodium agent method can effectively improve the coulombic efficiency of the whole battery, but the pre-sodium agent method cannot make the first-cycle coulombic efficiency of the whole battery reach 100%, which will cause capacity loss to a certain extent.

[0006] Although the direct contact method is simple, the metal sodium sheet is highly active and the operation process requires extremely high environmental moisture content. These pre-sodiumization technologies usually have difficulty controlling the structure and morphology of the SEI film formed in the first cycle, and it is difficult to regulate the SEI structure of the hard carbon negative electrode.

[0007] In view of the above problems existing in the prior art, the present invention combines many years of design and use experience in related fields to design a semi-solid sodium ion hard carbon negative electrode material and its preparation method and battery to overcome the above defects. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a semi-solid sodium ion hard carbon negative electrode material and a preparation method and a battery thereof, which reduce the activity of the pre-sodium material and greatly reduce the requirements for operating conditions. The Na-Sn-Al-O based compound formed on the hard carbon surface effectively improves the cycle performance of the whole battery, and the pre-sodium effect is remarkable.

[0009] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a semi-solid sodium ion hard carbon negative electrode material, comprising the following steps:

[0010] A Na-Sn metal sheet and a hard carbon negative electrode sheet containing Al2O3 powder are contacted in a first electrolyte environment for pre-sodiumization to obtain a negative electrode material, wherein the first electrolyte contains a sodium salt and an organic solvent.

[0011] Preferably, the mass ratio of Na:Sn in the Na—Sn metal sheet is 5:1-20:1.

[0012] Preferably, the sodium salt of the first electrolyte is one or more of NaFP6, NaClO4, NaTFSI, and NaDFOB.

[0013] Preferably, the preparation of the negative electrode material comprises the following steps:

[0014] T1: placing the hard carbon negative electrode sheet containing Al2O3 powder in a container, adding the first electrolyte into the container, so that the hard carbon negative electrode sheet containing Al2O3 powder is completely immersed in the first electrolyte;

[0015] T2: Laminating a Na-Sn metal sheet with uniform thickness onto a hard carbon negative electrode sheet containing Al2O3 powder, and applying a pressure of 1MPa-10MPa to the Na-Sn metal sheet to make the Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder fully contact;

[0016] T3: Continue to drip the first electrolyte into the container until the first electrolyte covers the upper surface of the Na—Sn metal sheet, and let it react for 12-24 hours to obtain the negative electrode material.

[0017] Preferably, the preparation of the hard carbon negative electrode sheet containing Al2O3 powder comprises the following steps:

[0018] S1: Mix hard carbon, Al2O3 powder and polyvinylidene fluoride evenly and apply a dispersant to form a slurry for negative electrode coating;

[0019] S2: baking the negative electrode of step S1 in a vacuum oven at 70-90° C. for 12-24 hours to obtain a hard carbon negative electrode sheet containing Al2O3 powder;

[0020] The mass ratio of the hard carbon, Al2O3 powder and polyvinylidene fluoride is 92-96:1-6:2-4.

[0021] Preferably, the mass ratio of the hard carbon, Al2O3 powder and polyvinylidene fluoride is 94:2:4.

[0022] Preferably, the dispersant is one or more of dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, tetramethylurea, dimethyl sulfoxide, triethyl phosphate, ethylene carbonate, and propylene carbonate.

[0023] A second aspect of the present invention provides a negative electrode material, which is prepared by the above-mentioned method for preparing a negative electrode material, and the surface of the negative electrode material contains a Na-Sn-Al-O structure.

[0024] A third aspect of the present invention provides a battery, the battery comprising the above-mentioned negative electrode material, positive electrode material and a second electrolyte;

[0025] The positive electrode material is a positive electrode sheet containing an O3 phase or a P2 phase layered oxide;

[0026] The second electrolyte contains a sodium salt and an organic solvent, and the sodium salt of the second electrolyte is one or more of NaFP6, NaClO4, NaTFSI, and NaDFOB.

[0027] Preferably, the capacity ratio of the negative electrode material to the positive electrode material is 1.05-1.1:1.

[0028] The invention is beneficial in that:

[0029] 1. The present invention performs pre-sodium treatment by contacting a Na-Sn metal sheet with a hard carbon negative electrode sheet containing Al2O3 powder, and forms a Na-Sn-Al-O structure on the surface of the hard carbon negative electrode sheet that can stably release active sodium. The structure has a synergistic effect and can serve as a thin and uniform SEI protective layer to increase the transmission speed of sodium ions, effectively inhibit the formation of sodium dendrites, avoid continuous consumption of electrolyte during the cycle, compensate for the loss of sodium ions in the layered oxide during the first cycle of charge and discharge, and improve the first cycle efficiency of the battery. At the same time, the hard carbon surface is separated from the electrolyte, effectively inhibiting the continuous side reaction between the electrolyte and the hard carbon.

[0030] 2. The present invention utilizes Sn to reduce the activity of Na, making the pre-sodium process controllable, reducing the environmental requirements of the highly active metal Na in the direct contact method, simplifying the negative electrode material preparation process, and reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the pre-sodiumization process in the present invention.

[0032] Figure 2 This is a transmission electron microscope test image of the hard carbon surface in the negative electrode material of Example 1 of the present invention.

[0033] Figure 3 The first charge and discharge curve and cycle performance curve of the semi-solid sodium battery of Example 1 of the present invention at a current of 0.1C are shown.

[0034] Figure 4 The first charge and discharge curve and cycle performance curve of the semi-solid sodium battery of Comparative Example 1 of the present invention at a current of 0.1C are shown.

[0035] Figure 5 This is a cycle performance curve of the semi-solid sodium battery of Comparative Example 2 of the present invention at a current of 0.1C. DETAILED DESCRIPTION

[0036] In order to facilitate understanding by those skilled in the art, the present invention is further described below in conjunction with specific embodiments.

[0037] The first aspect of the present invention provides a method for preparing a semi-solid sodium ion hard carbon negative electrode material, comprising the following steps:

[0038] The Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder are contacted in a first electrolyte environment for pre-sodiumization to obtain a negative electrode material, and the first electrolyte contains a sodium salt and an organic solvent. The present invention loads Na and Sn on the hard carbon negative electrode sheet by a direct contact method, and forms a Na-Sn-Al-O structure that can stably release active sodium with Al2O3 on the surface of the hard carbon negative electrode sheet. Sn can reduce the activity of Na, making the pre-sodium process controllable, so that a thin and uniform Na-Sn-Al-O structure can be controllably formed. The Na-Sn-Al-O structure serves as a SEI protective layer. On the one hand, it compensates for the loss of sodium ions in the positive electrode during the first cycle of battery charging and discharging, effectively inhibits the formation of sodium dendrites and improves the coulomb efficiency of the sodium ion full battery, improves the capacity of the negative electrode material and the energy density of the battery, and significantly improves the cycle performance of the battery; on the other hand, it separates the hard carbon surface from the electrolyte, effectively inhibiting the continuous side reaction between the electrolyte and the hard carbon.

[0039] Specifically, the preparation of the above negative electrode material includes the following steps:

[0040] T1: placing the hard carbon negative electrode sheet containing Al2O3 powder in a container, adding the first electrolyte into the container, so that the hard carbon negative electrode sheet containing Al2O3 powder is completely immersed in the first electrolyte;

[0041] T2: Laminating a Na-Sn metal sheet with uniform thickness onto a hard carbon negative electrode sheet containing Al2O3 powder, and applying a pressure of 1MPa-10MPa to the Na-Sn metal sheet to make the Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder fully contact;

[0042] T3: Continue to drip the first electrolyte into the container until the first electrolyte covers the upper surface of the Na—Sn metal sheet, and let it react for 12-24 hours to obtain the negative electrode material.

[0043] like Figure 1 As shown, in the present invention, pressure is applied to the Na-Sn metal sheet so that the Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder are completely attached to each other, so that the pre-sodium reaction occurs evenly on the hard carbon surface. The Na-Sn metal sheet is preferably rolled into a metal sheet of uniform thickness when used, and is cut into round pieces with the same diameter as the hard carbon negative electrode sheet. The mass ratio of Na:Sn in the Na-Sn metal sheet is preferably 5:1-20:1, and the sodium salt of the first electrolyte is one or more of NaFP6, NaClO4, NaTFSI, and NaDFOB.

[0044] The method of directly using Na metal sheet to pre-sodiumize the negative electrode has strict environmental requirements, requires anhydrous and oxygen-free conditions, and contact with the negative electrode may damage the surface of the negative electrode sheet. The present invention dilutes the Na content in the metal sheet by Sn in the Na-Sn metal sheet, reduces the activity of Na, thereby reducing the dependence of the preparation of the negative electrode material on the environment, and avoids the Na metal sheet from damaging the surface of the negative electrode sheet. The preparation of the negative electrode material in the present invention can be completed in a glove box or a battery drying room.

[0045] The preparation of the hard carbon negative electrode sheet containing Al2O3 powder in the present invention comprises the following steps:

[0046] S1: Mix hard carbon, Al2O3 powder and polyvinylidene fluoride (PVDF) evenly and apply a dispersant to form a slurry for negative electrode coating;

[0047] S2: The negative electrode sheet of step S1 is baked in a vacuum oven at 70-90° C. for 12-24 hours to obtain a hard carbon negative electrode sheet containing Al 2 O 3 powder.

[0048] Among them, the mass ratio of hard carbon, Al2O3 powder and polyvinylidene fluoride is preferably 92-96:1-6:2-4, and further preferably 94:2:4, and the dispersant is one or more of dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, tetramethyl urea, dimethyl sulfoxide, triethyl phosphate, ethylene carbonate and propylene carbonate.

[0049] A second aspect of the present invention provides a negative electrode material. The negative electrode material is prepared by the above-mentioned preparation method of the negative electrode material, and the surface of the negative electrode material contains a Na-Sn-Al-O structure.

[0050] The third aspect of the present invention provides a battery, which is a semi-solid sodium ion battery, comprising the above-mentioned negative electrode material, a positive electrode material and a second electrolyte, wherein the positive electrode material is a positive electrode sheet containing an O3 phase or a P2 phase layered oxide, and the O3 phase layered oxide includes but is not limited to NaCu 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、NaNi 2 / 5 Fe 1 / 5 Mn 2 / 5 O2, P2 phase layered oxides include but are not limited to Na 2 / 3Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na 2 / 3 Ni 2 / 5 Fe 1 / 5 Mn 2 / 5 The second electrolyte includes a sodium salt and an organic solvent, and the sodium salt of the second electrolyte is preferably one or more of NaFP6, NaClO4, NaTFSI, and NaDFOB, wherein the first electrolyte and the second electrolyte may be the same or different, and the capacity ratio of the negative electrode material to the positive electrode material is 1.05-1.1:1.

[0051] The present invention prepares a semi-solid sodium ion battery by an in-situ polymerization method, wherein the solvent used in the preparation process of the semi-solid sodium ion battery is preferably one or more of methyl carbonate, ethyl carbonate, methyl ethyl carbonate, and dimethyl carbonate, the polymerization monomer is preferably one or more of pentaerythritol triacrylate (PETA), polyethylene glycol diacrylate, and ethylene glycol diacrylate, and the initiator is preferably azobisisobutyronitrile and / or dimethyl azobisisobutyrate.

[0052] The specific embodiments are as follows

[0053] The conditions for the electrochemical performance test of the battery are as follows: the discharge test uses 0.1C to discharge to 1.5V, and then charges to 4.2V. The test voltage window is 1.5-4.2V. Example 1

[0054] S1: 94 g hard carbon, 2 g Al2O3 powder and 4 g PVDF were mixed evenly and coated into slurry with N-methylpyrrolidone (NMP) dispersant, and the slurry was coated on copper foil for negative electrode coating;

[0055] S2: drying the NMP on the copper foil slurry in a 60°C forced air oven, and then baking in a 80°C vacuum oven for 12 hours to obtain a negative electrode sheet;

[0056] T1: In a glove box, place the negative electrode sheet prepared in step S2 in a glass dish with the hard carbon side facing upward, and drop 40 μl of an electrolyte containing 1M NaClO4 (the solvent in the electrolyte is a mixture of methyl carbonate and ethyl carbonate, and the volume ratio of methyl carbonate / ethyl carbonate is 1:1) into the glass dish, so that the hard carbon on the negative electrode sheet is completely in contact with the electrolyte;

[0057] T2: Roll the Na-Sn metal sheet (mass ratio of 5:1) into uniform thickness and cut it into discs with a diameter of 16 mm. Completely fit the cut Na-Sn metal sheet on the hard carbon surface of the negative electrode sheet, and apply a pressure of 1 MPa to make the negative electrode sheet and the Na-Sn metal sheet fit better.

[0058] T3: 120 μL of electrolyte containing 1M NaClO4 was added dropwise around the Na-Sn metal sheet. The Na-Sn metal sheet and the hard carbon negative electrode sheet were completely immersed in the electrolyte and allowed to stand for 24 hours to obtain the negative electrode material.

[0059] This embodiment provides a negative electrode material prepared by the above preparation steps.

[0060] Preparation of the battery: 17 g of ethyl carbonate solvent, 2.2 g of polyethylene glycol diacrylate polymerization monomer, 42 g of an electrolyte containing 1M NaClO4 (the solvent in the electrolyte is a mixture of methyl carbonate and ethyl carbonate, and the volume ratio of methyl carbonate / ethyl carbonate is 1:1), and 0.13 g of azobisisobutyronitrile as an initiator are put into a container and mixed and stirred to form a polymer precursor solution;

[0061] The negative electrode material prepared in step T3 of this embodiment, Na 2 / 3 Cu 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 layered oxide positive electrode sheet (the capacity ratio of the negative electrode material to the positive electrode material is 1.05:1) and the separator are assembled, and then the polymer precursor solution and the electrolyte are injected. After the positive electrode material, the separator and the negative electrode material are infiltrated, they are placed in an oven and heated at 55°C for 24 hours to initiate a polymerization reaction to obtain a semi-solid sodium battery.

[0062] The sodium content in the negative electrode material prepared in this embodiment was tested by XPS test, and the molar ratio of sodium to aluminum in the negative electrode material was 1.03:1.

[0063] The microscopic morphology of the negative electrode material prepared in this embodiment was characterized using a transmission electron microscope. Figure 2As shown, it can be clearly seen that a thin and uniform Na-Sn-Al-O structure is formed on the hard carbon surface.

[0064] The electrochemical performance test was carried out on this embodiment. Figure 3 The first charge and discharge curve (left) and cycle performance curve (right) of the battery made of the negative electrode material obtained in Example 1. It can be seen from the figure that the first discharge specific capacity of the material is 138.13 mAh / g, the first cycle coulombic efficiency is close to 140%, and after 35 cycles, the discharge specific capacity is still greater than 100 mAh / g, and the coulombic efficiency is close to 100%. Example 2

[0065] S1: 46 g of hard carbon, 3 g of Al2O3 powder and 1 g of PVDF were mixed evenly and coated with dimethyl sulfoxide dispersant to form a slurry, and the slurry was coated on copper foil for negative electrode coating;

[0066] S2: Dry the dimethyl sulfoxide on the copper foil slurry in a 65°C forced air oven, and continue to dry in a 90°C vacuum oven for 12 hours;

[0067] T1: In a battery drying oven, place the negative electrode sheet prepared in step S2 in a glass dish with the hard carbon side facing upward, and drop 40 μl of an electrolyte containing 1M NaFP6 (the solvent is a mixture of methyl ethyl carbonate and dimethyl carbonate, and the volume ratio of methyl ethyl carbonate / dimethyl carbonate is 1:1) into the glass dish, so that the hard carbon on the negative electrode sheet is completely in contact with the electrolyte;

[0068] T2: Roll the Na-Sn metal sheet (mass ratio 10:1) into uniform thickness and cut it into discs with a diameter of 16 mm. Completely fit the cut Na-Sn metal sheet on the hard carbon of the negative electrode sheet, and apply a pressure of 5 MPa to make the negative electrode sheet and the Na-Sn metal sheet fit better.

[0069] T3: 120 μL of electrolyte containing 1M NaFP6 was added dropwise around the Na-Sn metal sheet. The Na-Sn metal sheet and the hard carbon negative electrode sheet were completely immersed in the electrolyte and allowed to stand for 18 hours to obtain the negative electrode material.

[0070] This embodiment provides a negative electrode material prepared by the above preparation steps.

[0071] Preparation of the battery: 9 g of methyl carbonate solvent, 0.9 g of PETA polymer monomer, 20 g of an electrolyte containing 1M NaFP6 (the solvent in the electrolyte is a mixture of methyl ethyl carbonate and dimethyl carbonate, and the volume ratio of methyl ethyl carbonate / dimethyl carbonate is 1:1), and 0.06 g of dimethyl azobisisobutyrate as an initiator are put into a container and mixed and stirred to form a polymer precursor solution;

[0072] The negative electrode material prepared in step T3 of this embodiment, Na 2 / 3 Ni 2 / 5 Fe 1 / 5 Mn 2 / 5 The O2 positive electrode sheet (the capacity ratio of the negative electrode material to the positive electrode material is 1.1:1) and the diaphragm are assembled, and then the polymer precursor solution and the electrolyte are injected. After the positive electrode material, the diaphragm and the negative electrode material are infiltrated, they are placed in an oven and heated at 60°C for 24 hours to initiate a polymerization reaction to obtain a semi-solid sodium battery.

[0073] The sodium content in the negative electrode material prepared in this embodiment was tested by XPS test, and the molar ratio of sodium to aluminum in the negative electrode material was 1.04:1.

[0074] The electrochemical performance test of this embodiment showed that the first discharge capacity of the battery of this embodiment was 136.0 mAh / g, the first cycle coulombic efficiency was 138%, and after 35 cycles, the discharge capacity was 100.3 mAh / g, and the coulombic efficiency was 100.2%. Example 3

[0075] S1: 48 g of hard carbon, 0.5 g of Al2O3 powder and 1.5 g of PVDF were mixed evenly and coated with dimethyl sulfoxide dispersant to form a slurry, and the slurry was coated on copper foil for negative electrode coating;

[0076] S2: Dry the dimethyl sulfoxide on the copper foil slurry in a 60°C forced air oven, and continue to dry in a 90°C vacuum oven for 12 hours;

[0077] T1: In a glove box, the negative electrode sheet prepared in step S2 is placed in a glass dish with the hard carbon side facing upward, and 50 μl of an electrolyte containing 1 M NaTFSI (the solvent is a mixture of dimethyl carbonate and ethyl carbonate, and the volume ratio of dimethyl carbonate / ethyl carbonate is 7:3) is added dropwise into the glass dish to make the hard carbon on the negative electrode sheet completely contact the electrolyte;

[0078] T2: Roll the Na-Sn metal sheet (mass ratio 20:1) into uniform thickness and cut it into discs with a diameter of 16 mm. Completely fit the cut Na-Sn metal sheet on the hard carbon of the negative electrode sheet, and apply a pressure of 10 MPa to make the negative electrode sheet and the Na-Sn metal sheet fit better.

[0079] T3: 120 μL of electrolyte containing 1M NaTFSI was added dropwise around the Na-Sn metal sheet. The Na-Sn metal sheet and the hard carbon negative electrode sheet were completely immersed in the electrolyte and allowed to stand for 12 hours to obtain the negative electrode material.

[0080] This embodiment provides a negative electrode material prepared by the above preparation steps.

[0081] Preparation of the battery: 12 g of dimethyl carbonate solvent, 1.3 g of ethylene glycol diacrylate polymerization monomer, 26 g of an electrolyte containing 1M NaTFSI (the solvent in the electrolyte is a mixture of methyl carbonate, ethyl carbonate and dimethyl carbonate, and the volume ratio of methyl carbonate / ethyl carbonate / dimethyl carbonate is 1:1:1), and 0.1 g of azobisisobutyronitrile as an initiator are put into a container and mixed and stirred to form a polymer precursor solution;

[0082] NaCu 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 layered oxide positive electrode sheet, the negative electrode material prepared in step T3 of this embodiment (the capacity ratio of the negative electrode material to the positive electrode material is 1.08:1) and the diaphragm are assembled, and then the polymer precursor solution and the electrolyte containing 1M NaTFSI are injected. After the positive electrode material, the diaphragm and the negative electrode material are wetted, they are placed in an oven and heated at 55°C for 24 hours to induce a polymerization reaction to obtain a semi-solid sodium battery.

[0083] The sodium content in the negative electrode material prepared in this embodiment was tested by XPS test, and the molar ratio of sodium to aluminum in the negative electrode material was 1.05:1.

[0084] The electrochemical performance test of this embodiment shows that the first discharge capacity of the battery of this embodiment is 122.13 mAh / g, the first cycle coulombic efficiency is 135%, and the discharge capacity after 35 cycles is 98.3 mAh / g, and the coulombic efficiency is 99.94%.

[0085] Comparative Example 1

[0086] The negative electrode material and the battery were prepared according to the method of Example 1, except that the negative electrode sheet of this comparative example was not subjected to pre-sodium treatment.

[0087] Comparative Example 2

[0088] 1.11 g Na-Sn metal powder (mass ratio of 5:1), 94 g hard carbon, 2.0 g Al2O3 powder and 4.0 g PVDF were mixed and coated with NMP dispersant to form a slurry, which was then coated on copper foil for negative electrode coating. The NMP on the copper foil slurry was dried in a blast oven at 60°C, and then continued to be dried in a vacuum oven at 80°C for 24 hours. The hard carbon pole piece was cut into a disc with a diameter of 16 mm using a cutting machine mold.

[0089] Preparation of the battery: 17 g of ethyl carbonate solvent, 2.2 g of polyethylene glycol diacrylate polymerization monomer, 42 g of an electrolyte containing 1M NaClO4 (the solvent in the electrolyte is a mixture of methyl carbonate and ethyl carbonate, and the volume ratio of methyl carbonate / ethyl carbonate is 1:1), and 0.13 g of azobisisobutyronitrile as an initiator are put into a container and mixed and stirred to form a polymer precursor solution;

[0090] The negative electrode material prepared in this comparative example, Na 2 / 3 Cu 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 layered oxide positive electrode sheet (the specific capacity of the negative electrode material and the positive electrode material is 1.05:1) and the separator are assembled, and then the polymer precursor solution and the electrolyte are injected. After the positive electrode sheet, the separator and the negative electrode sheet are soaked, they are placed in an oven and heated at 55°C for 24 hours to induce a polymerization reaction to obtain a semi-solid sodium battery.

[0091] The electrochemical performance of Comparative Example 1 and Comparative Example 2 was tested, and the results were Figure 4 , Figure 5 .

[0092] Comparing Example 1 with Comparative Example 1, Figure 3 and Figure 4 It can be seen that the discharge capacity of the battery assembled with the hard carbon negative electrode without pre-sodium treatment is only 81.76mAh / g, and the first cycle coulombic efficiency is 75%, which is much lower than the first cycle coulombic efficiency of the battery in Example 1. In addition, the discharge specific capacity of Comparative Example 1 gradually decreases with the increase of the number of cycles, and the discharge specific capacity is close to 10mAh / g at 35 times. It can be seen that the electrolyte of the semi-solid sodium ion full battery composed of the negative electrode without pre-sodium treatment is continuously consumed during the cycle, indicating that the pre-sodium effect of the negative electrode material prepared by the present invention is good, which can make up for the loss of sodium ions in the positive electrode material during the first cycle of charge and discharge, reduce the consumption of electrolyte during the cycle, and improve the coulombic efficiency of the sodium ion full battery.

[0093] Comparing Example 1 with Comparative Example 2, Figure 5It can be seen that the discharge specific capacity of Comparative Example 2 is 105 mAh / g, and the first cycle coulomb efficiency is 120%. The discharge specific capacity gradually decreases during the cyclic use process, and drops to about 70 mAh / g after 35 cycles. The discharge specific capacity and the first cycle coulomb efficiency are lower than those of Example 1, indicating that the pre-sodiumization effect of the negative electrode material obtained by physically mixing the Na-Sn metal sheet and the hard carbon negative electrode is not as good as the negative electrode material prepared by the direct contact method of the present invention. This is because the Na-Sn-Al-O structure on the surface of the negative electrode material prepared by the present invention has a synergistic effect, which can improve the problem of continuous consumption of active sodium in subsequent cycles caused by the uneven SEI structure formed in the first cycle, and provide a thin and uniform SEI structure while supplementing sodium ions, effectively improving the coulomb efficiency and energy density of the sodium ion battery, improving the cycle performance of the battery, and effectively inhibiting the continuous side reaction between the electrolyte and the hard carbon negative electrode.

[0094] It should be understood that the purpose of these embodiments is only to illustrate the present invention and is not intended to limit the protection scope of the present invention. In addition, it should also be understood that after reading the technical content of the present invention, those skilled in the art can make various changes, modifications and / or variations to the present invention, and all of these equivalent forms also fall within the protection scope defined by the claims attached to this application.

Claims

1. A method for preparing a semi-solid sodium ion hard carbon negative electrode material, characterized in that: The following steps are involved: The Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder are contacted in a first electrolyte environment for pre-sodiumization to obtain a negative electrode material, wherein the first electrolyte contains a sodium salt and an organic solvent; The preparation of the negative electrode material comprises the following steps: T1: placing the hard carbon negative electrode sheet containing Al2O3 powder in a container, adding the first electrolyte into the container, so that the hard carbon negative electrode sheet containing Al2O3 powder is completely immersed in the first electrolyte; T2: Laminating a Na-Sn metal sheet with uniform thickness onto a hard carbon negative electrode sheet containing Al2O3 powder, and applying a pressure of 1MPa-10MPa to the Na-Sn metal sheet to make the Na-Sn metal sheet and the hard carbon negative electrode sheet containing Al2O3 powder fully contact; T3: Continue to drip the first electrolyte into the container until the first electrolyte covers the upper surface of the Na—Sn metal sheet, and let it react for 12-24 hours to obtain the negative electrode material.

2. The method for preparing a semi-solid sodium ion hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of Na:Sn in the Na-Sn metal sheet is 5:1-20:

1.

3. The method for preparing a semi-solid sodium ion hard carbon negative electrode material according to claim 1, characterized in that: The sodium salt of the first electrolyte is one or more of NaFP6, NaClO4, NaTFSI, and NaDFOB.

4. The method for preparing a semi-solid sodium ion hard carbon negative electrode material according to claim 1, characterized in that: The preparation of the hard carbon negative electrode sheet containing Al2O3 powder comprises the following steps: S1: Mix hard carbon, Al2O3 powder and polyvinylidene fluoride evenly and apply a dispersant to form a slurry for negative electrode coating; S2: baking the negative electrode of step S1 in a vacuum oven at 70-90° C. for 12-24 hours to obtain a hard carbon negative electrode sheet containing Al2O3 powder; The mass ratio of the hard carbon, Al2O3 powder and polyvinylidene fluoride is 92-96:1-6:2-4.

5. The method for preparing a semi-solid sodium ion hard carbon negative electrode material according to claim 4, characterized in that: The mass ratio of the hard carbon, Al2O3 powder and polyvinylidene fluoride is 94:2:

4.

6. The method for preparing a semi-solid sodium ion hard carbon negative electrode material according to claim 4, characterized in that: The dispersant is one or more of dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, tetramethylurea, dimethyl sulfoxide, triethyl phosphate, ethylene carbonate, and propylene carbonate.

7. A negative electrode material, characterized in that: The negative electrode material is prepared by the negative electrode material preparation method according to any one of claims 1 to 6, and the surface of the negative electrode material contains a Na-Sn-Al-O structure.

8. A battery, characterized in that: The battery comprises the negative electrode material, the positive electrode material and the second electrolyte as claimed in claim 7; The positive electrode material is a positive electrode sheet containing an O3 phase or a P2 phase layered oxide; The second electrolyte contains a sodium salt and an organic solvent, and the sodium salt of the second electrolyte is one or more of NaFP6, NaClO4, NaTFSI, and NaDFOB.

9. A battery according to claim 8, characterized in that: The capacity ratio of the negative electrode material to the positive electrode material is 1.05-1.1:1.

Citation Information

Patent Citations

  • Method for pre-lithiation / pre-sodiation of negative electrode, pre-lithiated / pre-sodiated negative electrode, and lithium secondary battery comprising same

    US20220293908A1

  • Negative electrode for sodium-ion secondary batteries, and sodium-ion secondary battery

    WO2024135593A1

Cited By

  • Sodium pre-supplementing hard carbon negative electrode material as well as preparation method and application thereof

    CN122224808A